Passiflora calypilosa, a new species of Passiflora sect. Elkea (Passifloraceae) from the Andes of Colombia - Kuethe, J.r.; Bernal, Hernan Dario (Phytotaxa, 2020)
A new species from the Andes of Colombia is described. Passiflora calypilosa sp. nov. from supersection Tacsonia, section Elkea is morphologically closely related to Passiflora crispolanata from Boyacá, Colombia, and the polymorphic varieties of Passiflora lanata and Passiflora adulterina. The new species clearly differs from them in the fully tomentose hypanthium after which it is named and the densely hirsute ovary. Further, it appears to be restricted to a small area South-west of Bogota, Cundinamarca, Colombia. The morphology, distribution and ecology of the new species is compared and discussed below.